(3GdeKdKs - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3QCjJ LeGYI GdeJJHYjf dWdHI GdCOH jhdYhf HcJGH GdeKdK GdefShH Edi bWQH hEfeG fYJO eKdKkG ai cJGHfG gPG eG GJabJ ChRGfg hJYGOdJ CbSGeg s
(3BNQgG (B:s
(3hUQ GdLfOH jUQ HGdcSQ hcPdc GdHGH hGdQLd hGdQMi hGdCfjGH hfMhgG hUQ GdOQGge HGdVe ced HMeO dGdg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B198 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs